Level of Informal Reasoning (IR) of State Senior High School Students Throughout Semarang City based on Rational Patterns - Ipah Budi Minarti; Fenny Roshayanti; Sri Astuti (Abjadia, 2023)
This aiming of the research is to know about the level Informal Reasoning (IR) of Senior High School in Semarang City based on Rational. This is a Qualitative Descriptive research. The population of this research is students of XI class of all Senior High School in Semarang city. Sample was find out by used proportionate random sampling technique. Sample of the research was the students of XI MIPA from 10 schools in Semarang City which total was 340 students. The method of collect data used by Informal Reasoning test, interview by teacher and the students and also observation. The highest precentage of Informal Reasoning according to Rational Pattern (44,81%).